Electric drives of traction rolling stocks with AC motors - Lingaitis, Leonas P.; Liudvinavičius, Lionginas (Transport, 2006)
The paper considers the variation of circuit design of the electric drives in traction rolling stocks when traditional DC electric machines are replaced with AC electric machines. Simplified circuit diagrams of the electric drives using electric machines of non‐commutator type are offered. Operational defects of DC traction engines are weighed against some positive characteristics of direct current series excitation in traction engines, determining their extensive use in the electric drives of traction rolling stocks. However, the rapid development of semiconductor devices, e.g. thyristors and IGBT transistors, led to the creation of a great variety of semiconductor inverters. This made it possible to develop an autonomous three‐phase power supply system for diesel locomotives and algorithms for the AC traction motors and to obtain engine characteristics matching the tractive force by using voltage frequency and current inverters. A mathematical justification of the engine torque and tractive force control as well as its particular characteristics is provided. The graphs demonstrating the particular ways of changing the electrical parameters of an asynchronous motor with a squirrel‐cage rotor are also presented. First Published Online: 27 Oct 2010